Practicing Numeracy Literacy-Based Learning to Enhancing Students’ Understanding in Mathematics at 5th Grade Students of Madrasah Ibtidaiyah - Pratiwi, Inne Marthyane; Mahmud, Muhammad Rifqi; Fauziah, Tia Nur; Mubarok, Zaenal Mutakin (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Numeracy and literacy skills among some madrasah ibtidaiyah students are still low. According to public education report in 2022 at the elementary level showed that numeracy skills were still under the minimum competency standard. The cause of students' low in numeracy and literacy skill was the use of teaching materials that were not relevant to encourage their numeracy and literacy skills. Therefore, the aim of the community service activity was to provide training in making teaching materials based on numeracy and literacy strategies at one of the ibtidaiyah madrassas in Bandung City. This program applied a Participatory Action Research (PAR) with the model used, namely contextual action research. The results were the teachers grasped more understanding in numeracy literacy-based teaching materials, especially math teachers, numeracy literacy-based teaching materials were obtained, and the students' understanding of the basic concepts of numeracy and literacy was increase. The follow-up to this program was the dissemination of teaching materials to others madrasah ibtidaiyah in the city of Bandung so that these teaching materials can be implemented.